Enemies with benefits? Violent rivalry and terrorist group longevity. (January 2015) - Phillips, Brian J
Terrorist organizations often attack each other, but we know little about how this affects the involved groups. Some states encourage or turn a blind eye toward terrorist group interorganizational violence, hoping that it destroys at least one of the groups involved. This article argues that – contrary to the wishes of such governments – violent rivalries can contribute to the longevity of participating terrorist groups. Violent rivalries encourage civilians to take a side, inspire innovation, provide new incentives to group members, and spoil peace talks. Some of these mechanisms should be especially likely between rivals of different political goals (interfield rivalries), instead of between rivals seeking the same primary goal (intrafield rivalries). Illustrative cases in Colombia and Northern Ireland show that the theorized mechanisms occur in diverse environments. Quantitative global analysis of terrorist groups from 1987 to 2005, using original data on interorganizational violence, suggests that violent rivalries are generally associated with group longevity. Further analysis suggests that when rivalries are disaggregated by type, only interfield rivalries are positively associated with group longevity. Participation in violent rivalry is never found to increase a group's chance of ending. The results suggest the importance of studying interorganizational dynamics, and raise questions about the notion of encouraging a violent rivalry as a way to hurt an involved terrorist group.